PENGGUNAAN PENDEKATAN CONTEXTUAL TEACHING LEARNING BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Irwanto Irwanto; Marliah Marliah (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to (1) determine the motivation improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration, (2) determine the learning achievement improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration, (3) determine the correlation between motivation improvement and learning achievement improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration. The method used in this research was a quasi-experimental model, and the design used was a one-group pretest-postest design. The research samples were 30 fifth grade students. Based on the research, the results showed: (1) there was a motivation improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration, (2) there was a learning achievement improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration, (3) there was no correlation between motivation improvement and learning achievement improvement in students whose teaching used interactive multimedia-based Contextual Teaching Learning (CTL) in science subject for the topic of respiration.